THE IMPLEMENTATION OF THINK PAIR SHARE WITH FLIPGRID TOOL IN IMPROVING STUDENTS’ SPEAKING ABILITY - Kadek Widi Margana Yasa; I Gde Putu Agus Pramerta; Luh Ketut Sri Widhiasih (Academic Journal on English Studies (AJOES), 2023)
Speaking is a crucial language skill to be mastered in this era. However, most of the students faced problems with their speaking ability. It happens at SMP (SLUB) Saraswati 1 Denpasar. Thus, this study aimed at finding out the improvement of the eighth-grade student with the implementation of Think Pair Share (THS) combined with Flipgrid. Classroom Action Research was used as the research method. Pre-test, post-test, and questionnaire were administered to collect data. The result of the post-tests I and II were 79.9 and 79.24. Moreover, the questionnaire result showed that the students were actively engaged and motivated after the implementation of TPS combined with Flipgrid. To sum up, the present classroom action research proved that the students’ speaking ability could be improved. In Addition, the subjects also responded positively. The implication of the study is a fun and enjoyable ambiance in the teaching and learning process should be accommodated in the speaking activities.